A companion to forensic anthropology - Dirkmaat, Dennis (Blackwell Companions to Anthropology, 2015)
A Companion to Forensic Anthropology explores the latest theoretical and methodological work in the field, and includes thorough and up-to-date bibliographies. A wide range of international experts provide a comprehensive assessment of the field of forensic anthropology